"The Bell Beaker Culture in All its Forms" Proceedings of the 22nd Meeting of 'Archéologie et Gobelets' 2021 (Geneva, Switzerland) - Abegg, Claudine (Archaeopress Publishing, 2022)
Proceedings of the 22nd meeting of the 'Archéologie et Gobelets' Association which took place in Geneva, Switzerland in January 2021. The book is structured in three parts: Archaeological Material, Funerary Archaeology and Anthropology, and Reconstructing Bell Beaker Society.